1986
DOI: 10.1128/mcb.6.10.3320
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Saccharomyces cerevisiae inositol-1-phosphate synthase (INO1) gene is regulated by factors that affect phospholipid synthesis.

Abstract: The INO1 gene of Saccharomyces cerevisiae encodes the regulated enzyme inositol-1-phosphate synthase, which catalyzes the first committed step in the synthesis of inositol-containing phospholipids. The expression of this gene was analyzed under conditions known to regulate phospholipid synthesis. RNA blot hybridization with a genomic clone for INO1 detected two RNA species of 1.8 and 0.6 kb. The abundance of the 1.8-kb RNA was greatly decreased when the cells were grown in the presence of the phospholipid prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
206
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(218 citation statements)
references
References 18 publications
(36 reference statements)
10
206
2
Order By: Relevance
“…For example, it was originally reported that INO1 expression is repressed by an additional 2-3-fold in cells grown in inositol-containing medium when choline is present compared with cells grown in inositol-containing medium when choline is absent (16). Similar simultaneous effects of inositol and choline have also been observed for CHO1 (17,20), OP13 (21), CHO2 (21), CKI1 (52), and CPT1 (53).…”
Section: Global Analysis Of Inositol and Choline On Gene Expressionsupporting
confidence: 56%
See 2 more Smart Citations
“…For example, it was originally reported that INO1 expression is repressed by an additional 2-3-fold in cells grown in inositol-containing medium when choline is present compared with cells grown in inositol-containing medium when choline is absent (16). Similar simultaneous effects of inositol and choline have also been observed for CHO1 (17,20), OP13 (21), CHO2 (21), CKI1 (52), and CPT1 (53).…”
Section: Global Analysis Of Inositol and Choline On Gene Expressionsupporting
confidence: 56%
“…Strains were maintained on yeast extract/peptone/dextrose (YPD) plates (1% yeast extract, 2% bactopeptone, 2% glucose, and 2% agar). All experiments were performed using chemically defined synthetic complete media (16,40), containing (per liter): 20 g of glucose, 5 g of ammonium sulfate, 1 g of potassium phosphate, 0.5 of g magnesium sulfate, 1 g of sodium chloride, 0.1 g of calcium chloride, 0.5 mg of boric acid, 0.04 mg of cupric sulfate, 0.1 mg of potassium iodide, 0.2 mg of ferric chloride, 0.4 mg of manganese sulfate, 0.2 mg of sodium molybdate, 0.4 mg of zinc sulfate, 2 g of biotin, 400 g of calcium pantothenate, 2 g of folic acid, 400 g of niacin, 200 g of p-aminobenzoic acid, 400 g of pyridoxine hydrochloride, 200 g of riboflavin, 400 g of thiamine, 20 mg of adenine sulfate, 20 mg of arginine, 20 mg of histidine, 60 mg of leucine, 230 mg of lysine, 20 mg of methionine, 300 mg of threonine, 20 mg of tryptophan, and 40 mg of uracil. Where indicated, media were supplemented with 75 M myo-inositol and/or 1 mM choline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of INO1 and OIP3 had been shown previously to be regulated at the level of transcript abundance. The rate-limiting step in inositol phospholipid biosynthesis is mediated by the INO1 gene product (30,31). Therefore, we propose that PC synthesis in yeast cells is promoted by Me 2 SO exposure, because there was significant enhancement in the levels of mRNA for INO1 and OPI3 as shown in Table I and Fig.…”
Section: Me 2 So Concentration and Duration Of Exposure-s Cerevisiaementioning
confidence: 99%
“…RNA probes for northern analysis were synthesized using the Gemini II core system from plasmids linearized with a restriction enzyme as follows (plasmid, restriction enzyme, RNA polymerase): pJH310, HindIII, T7 (INO1); pAB309, EcoRI, SP6 (TCM1). 30 Hybridization with the pJH310-derived probe 31 detects a single 1.8-kb INO1 transcript, which is not detected in RNA from strains containing a deletion of the INO1 gene. The results of northern blot hybridization were visualized by autoradiography, and relative levels of INO1 and TCM1 were quantitated by phosphorimaging.…”
Section: Measurement Of Ino1 Expressionmentioning
confidence: 99%